Results for retarded nonlinear integral inequalities with mixed powers and their applications to delay integro-differential equations - Shakoor, А.; Samar, M.; Athar, T.; Saddique, M. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.9We present new retarded nonlinear integral inequalities with mixеd powers. The obtained inequalities can be used to study the boundedness and global existence of the solutions of  integro-differential equation with delay and Volterra-type integral equation with delay.  These inequalities extend some  results available in the  literature.  Finally, we present two examples to demonstrate the usefulness of our main results.